Eur Oral Res 2021
DOI: 10.26650/eor.20210004
|View full text |Cite
|
Sign up to set email alerts
|

Bond strength of metal brackets to feldspathic ceramic treated with different surface conditioning methods: an in vitro study

Abstract: Purpose To compare MEP which is originally manufactured for increasing bond strength between organic resins and ceramic with conventional surface treatment methods in preparation of leucite-reinforced FC surfaces regarding shear bond strength (SBS) of stainless steel brackets and the mode of bond failure. Materials and Methods Forty specimens that were fabricated from FC material and glazed were randomly assigned to four surface conditioning methods: (1) CoJet Sand; (2) MEP; (3) HF acid etching followed by sil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
2
4
0
Order By: Relevance
“…Karan et al reported similar SBS values after pretreatment of different silicate ceramics with either CoJet or 50-μm aluminia oxide sandblasting followed by HF and thermo cycling [48]. In a further investigation pretreatment of LEU with CoJet resulted in significant higher SBS values after thermal cycling compared to HF [49], and slightly higher after 24 h [44] which is in accordance with the present results, although the difference we found were not significant. All of the above described studies used metal brackets and not ceramic, as in the present investigation.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Karan et al reported similar SBS values after pretreatment of different silicate ceramics with either CoJet or 50-μm aluminia oxide sandblasting followed by HF and thermo cycling [48]. In a further investigation pretreatment of LEU with CoJet resulted in significant higher SBS values after thermal cycling compared to HF [49], and slightly higher after 24 h [44] which is in accordance with the present results, although the difference we found were not significant. All of the above described studies used metal brackets and not ceramic, as in the present investigation.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to our findings González-Serrano et al described lower SBS values after conditioning of LiSi with MEP in comparison to HF, but the differences were not significant after 24 h. They also found a very little reduction of SBS after HF treatment and thermal cycling, but a significant reduction after MEP pretreatment [43]. In contrast to our finding, Duygu et al reported slightly higher SBS values after pretreatment of LEU with MEP in comparison to HF [44]. Many studies comparing different pretreatment methods used airborne particle abrasion with alumina powder as an alternative for HF [45,46].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, achieving an ideal bond strength with extremely hard and durable monolithic zirconia remains challenging in adult orthodontic treatment [ 18 ]. In clinical practice, the bond strength of brackets to ceramic restorations should be sufficiently high to withstand intraoral masticatory forces and orthodontic forces during treatment while also being low enough to prevent permanent damage to the ceramic surface during bracket removal at the end of treatment [ 7 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has the possibility of irritating intraoral tissues and causing mechanical damage to soft tissues. Additionally, there is a risk of inhalation of aluminum oxide particles [ 22 ]. However, these risks can be minimized in clinical practice by using effective aspiration devices to minimize the dispersion of particles.…”
Section: Discussionmentioning
confidence: 99%